Managing post stroke hyperglycaemia: moderate glycaemic control is better? An update - Wan Sulaiman, Wan Aliaa; Hashim, Hasnur Zaman; Che Abdullah, Shahrin Tarmizi; Hoo, Fan Kee; Basri, Hamidon (IfADo - Leibniz Research Centre for Working Environment and Human Factors, 2014)
Post stroke hyperglycaemia (PSH) is prevalent in acute ischaemic stroke (AIS) patients and it has been associated with a dismal outcome of death and disability. Insulin has been proven to attenuate glucose effectively in stroke patients, thus many trials over the years had studied the efficacy of intensive treatment aiming at normalization of blood sugar level in order to improve the bleak outcomes of PSH. However, tight glycaemic control failed to be translated into clinical benefits and the outcomes are no different from the conventional approach, despite the costly healthcare expenditure invested. On the contrary, it brings more significant harm than the intended benefit, as 1 in every 9 treated patients had symptomatic hypoglycaemia. Thus, the benefits of tight glucose control, if any, are overshadowed by this potential risk of hypoglycaemia causing permanent neurological injury. Therefore, international practice guidelines recommend for less aggressive treatment to maintain blood glucose level within an appropriate range in AIS patients. However, there are limited details for stroke-specific glycaemic management and this made management of PSH particularly difficult. This review is to discuss and provide suggestions concerning glycaemic control in acute ischaemic stroke; the direction of its future prospective clinical trials and the treatment strategy required based on recent literature.